The impact of vacuum-assisted excision in the management of indeterminate B3 lesions in the NHS Breast Screening Programme in England. Issue 6 (June 2021) - Sharma, N.; Cornford, E.; Cheung, S.; Price, H.; Kearins, O.
Abstract : AIM: To assess the impact of vacuum-assisted excision (VAE) on the management of B3 lesions in the England NHS Breast Screening Programme following an update of national guidance. A secondary aim was to investigate the histological features of malignancies resulting from upgrade of B3 lesions by either VAE or surgery. MATERIALS AND METHODS: The study population was all women recalled for assessment after breast screening who had a wide-bore needle biopsy with a B3 result over the period 01/04/2018 to 31/03/2019. Data were extracted from the National Breast Screening Service (NBSS) computer system at unit level. Women with a B3 result were split into those with and without atypia. The upgrade rates and histological features of malignancies in the different groups were analysed. RESULTS: In total, 2, 234, 514 women attended for screening between 1/4/218 and 31/3/2019, 84, 559 women were referred to assessment, and of those 40, 037 women had a core biopsy resulting in 3, 355 were B3 lesions (8.38%). Within these, 556 cancers were diagnosed, giving an upgrade rate of 16.57% (556/3, 355). The upgrade for B3 lesions with atypia was significantly higher than for B3 lesions without atypia (29.1% versus 13.3%, p< 0.001). CONCLUSION: The introduction of the new B3 guidelines has resulted in 73.8% of B3 lesions with atypia and 65.1% of B3 lesions with no atypia having VAE rather than surgery. The data highlights the importance of managing these indeterminate lesions appropriately with an overall upgrade rate of 16.57%. Highlights: In the England Breast Screening Programme the upgrade rate of B3 lesions is 16.57%. The proportion of women having surgery has declined due to the guidelines. 73.8% of B3 lesions with atypia and are having VAE rather than surgery. 65.1% of B3 lesions with no atypia are having VAE rather than surgery.